Sistem Informasi Penerbitan Surat Izin Berlayar Menggunakan Metode First In First Out (FIFO) di Kantor Kesyahbandaran dan Otoritas Pelabuhan Utama Belawan - Muhammad Reynaldi; Ria Eka Sari (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
The issuance of sailing permits at the Belawan Harbormaster and Main Port Authority Office (KSOP) still faces various obstacles, particularly related to the accumulation of application files, irregular queues, and long document processing times. These problems impact service efficiency and user satisfaction. This study aims to design and implement a web-based information system that applies the First In First Out (FIFO) method to improve the effectiveness of the sailing permit issuance process. The study uses a Waterfall approach, which includes the stages of needs analysis, system design, implementation, and functional testing using Blackbox Testing. The results show that the application of the FIFO method to the web-based system is able to organize the service flow more fairly based on the chronological order of submissions, thereby reducing the risk of service discrimination and minimizing input errors that previously often occurred in manual processes. The system is also able to accelerate the process of verification, data validation, and printing of permits, resulting in more efficient service times. In addition, transparency of the service process is increased through real-time monitoring of application status. Overall, the information system developed has been proven to improve service quality and public trust in the performance of KSOP Belawan